STRATEGI KOMUNIKASI KOMPAS TV DALAM MENYAMPAIKAN BERITA AGAMA SECARA AKURAT - Ni'matus Saadah; Primi Rohimi (Fakultas Komunikasi dan Desain Program Studi Komunikasi dan Penyiaran Islam, 2024)
This research examines the communication strategies used by Kompas TV in presenting religious news accurately. This research aims to identify and analyze the strategies used by Kompas TV in reporting religious news, with a focus on how they ensure accuracy and sensitivity in their reporting. This research uses a qualitative descriptive method while data is collected through observation, interviews and documentation. The findings show that Kompas TV uses various strategies, including framing, narrative, and perspective, to ensure accuracy and sensitivity in their reporting. This study concludes that effective communication strategies are very important for media organizations such as Kompas TV in managing and presenting religious news accurately and avoiding controversy. The implications of this research are very significant, namely contributing to improving journalism practices in Indonesia, especially in covering religious news.